2009
DOI: 10.3748/wjg.15.457
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for colonic diverticular bleeding: A Westernized community based hospital study

Abstract: Beside nonsteroidal anti-inflammatory steroid drug use, antihypertensive medication and concomitant arteriosclerotic diseases are risk factors for colonic diverticular hemorrhage. Our results support the hypothesis of an altered arteriosclerotic vessel as the source of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
5
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 19 publications
5
66
5
5
Order By: Relevance
“…abscess, perforation). In addition, three small case-control studies of diverticular bleeding found no relationship with alcohol intake [34,35,36]. …”
Section: Alcoholmentioning
confidence: 99%
“…abscess, perforation). In addition, three small case-control studies of diverticular bleeding found no relationship with alcohol intake [34,35,36]. …”
Section: Alcoholmentioning
confidence: 99%
“…Previous studies have also reported very low mortality rates associated with CDB (2,5,13,16,17). This indicates that mortality is not a major outcome of CDB and that the therapeutic measures applied to these patients are in fact effective.…”
Section: Discussionmentioning
confidence: 85%
“…Mortality rates related to CDB are low, varying from 0 to 7% across studies (2,5,13,16,17). Severe bleeding is more difficult to assess, since its definition is not clearly established, and therefore different studies have used different criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hypercholesterolaemia was retrieved from the EPR and defined as elevated levels of cholesterol in the bloodstream compared with the reference range and requiring treatment. Usage of regularly prescribed medications, such as aspirin 22 and steroids, 23 was also recorded as these have been shown to be independent risk factors for diverticular haemorrhage.…”
Section: Ethnicity and Comorbiditiesmentioning
confidence: 99%